Erbium Single-Band Nanothermometry in the Third Biological Imaging Window: Potential and Limitations - Hazra, Chanchal; Skripka, Artiom; Ribeiro, Sidney J. L. [UNESP]; Vetrone, Fiorenzo (Wiley, 2020)
Near-infrared (NIR) nanothermometers are sought after in biomedicine when it comes to measuring temperatures subcutaneously. Yet, temperature sensing within the third biological imaging window (BW-III), where the highest contrast images can be obtained, remains relatively unexplored. Here, LiErF4/LiYF4 rare-earth nanoparticles (RENPs) are studied as NIR nanothermometers in the BW-III. Under 793 nm excitation, LiErF4/LiYF4RENPs emit around 1540 nm, corresponding to the 4I13/2 → 4I15/2radiative transition of Er3+. The fine Stark structure of this transition allows to delineate intensity regions within the emission band that can be used for single-band ratiometric nanothermometry. These nanothermometers have a relative temperature sensitivity of ≈0.40% °C−1. The temperature-dependent energy transfer to the surrounding solvent molecules plays a significant role in the thermometric properties of the RENPs. In addition, Ce3+ions are doped in the core of the RENPs to examine whether it affects the NIR emission and temperature sensitivity. Ce3+ at 1 mol% marginally influences the downshifting emission intensity of the RENPs, yet increases the relative thermal sensitivity to ≈0.45% °C−1. Furthermore, Ce3+ quenches the visible upconversion emission of the RENPs. Together, LiErF4:Ce3+/LiYF4RENPs enable single-band photoluminescence nanothermometry in the BW-III, with the future possibility of its integration within multifunctional decoupled theranostic nanostructures.
Keywords: biological windows; LiErF 4; nanothermometry; near-infrared emission; rare-earth nanoparticles; upconversion